Probabilistic teleportation without loss of information - Roa, Luis; Groiseau, Caspar (Physical review. A, Atomic, molecular, and optical physics, 2015)
We found a scheme for teleporting probabilistically an unknown pure state with optimal probability and without losing the information of the state to be teleported. Accordingly, without having to have copies of the unknown state, the teleportation process can be repeated as many times as one has available quantum channels. Thus, although the quantum channels have a weak entanglement, teleportation is achievable with a high number of repetitions, whereas for channels with strong entanglement only a small number of repetitions are required to guarantee successful teleportation.
Published 30 January 2015, corrected 4 February 2015
Gesehen am 02.07.2020